2009
DOI: 10.1177/0734904109341030
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Dynamics of a Co-flow Diffusion Flame with High Expansion Aqueous Foam

Abstract: A time-dependent, moving boundary, multiphase Navier-Stokes model is developed to study the effects of aqueous foam with high air-to-water volume ratio (expansion ratio, Ex) on a jet diffusion flame. The flame is formed by combusting a steady flow of propane gas. Both the shape and velocity of the foam surface are affected by evaporation and injection rates, and are obtained by volume of fluid method. The evaporation at the advancing foam front releases water vapor as well as a significant amount of air into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…An ideal foam will expand rapidly with sufficient mobility to maneuver around obstacles and cover a large area of the threat space to quickly reach the fire. Although the overall fire suppression mechanism is unknown, three mechanisms have been suggested based on observations and empirical understanding [4]. Water contained in the foam can evaporate as the foam approaches and interacts with a flame, resulting in (1) heat absorption as well as (2) dilution of oxygen available to the fire.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal foam will expand rapidly with sufficient mobility to maneuver around obstacles and cover a large area of the threat space to quickly reach the fire. Although the overall fire suppression mechanism is unknown, three mechanisms have been suggested based on observations and empirical understanding [4]. Water contained in the foam can evaporate as the foam approaches and interacts with a flame, resulting in (1) heat absorption as well as (2) dilution of oxygen available to the fire.…”
Section: Introductionmentioning
confidence: 99%
“…Determining these rates is critical for optimizing HiEx foam systems, especially considering the strict space and weight penalties for shipboard usage. Recently, Ananth and Farley [3] developed a computational model to predict the dynamics of flame suppression in a cup burner. They showed that an increased foam injection rate increases the degree of suppression and that water evaporation and smothering effects also play key roles in extinction.…”
Section: Introductionmentioning
confidence: 99%